2008
DOI: 10.2307/25148868
|View full text |Cite
|
Sign up to set email alerts
|

Buyer Intention to Use Internet-Enabled Reverse Auctions: The Role of Asset Specificity, Product Specialization, and Non-Contractibility

Abstract: Information technology enabled exchanges in electronic markets have significant implications for buyer-supplier rela-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 84 publications
0
46
0
Order By: Relevance
“…Information systems researchers have actively been seeking to understand how to encourage participation in online auctions (e.g., Choudhury et al 1998, Mithas et al 2008. Further, by studying how sellers can selectively allocate products to the e-channel, our research contributes to work that seeks to understand how changes to auction design influence seller and buyer surplus (e.g., Jap 2003Jap , 2007.…”
Section: Business-to-business Online Auctionsmentioning
confidence: 99%
“…Information systems researchers have actively been seeking to understand how to encourage participation in online auctions (e.g., Choudhury et al 1998, Mithas et al 2008. Further, by studying how sellers can selectively allocate products to the e-channel, our research contributes to work that seeks to understand how changes to auction design influence seller and buyer surplus (e.g., Jap 2003Jap , 2007.…”
Section: Business-to-business Online Auctionsmentioning
confidence: 99%
“…Research has found that product specialization has explanatory power for reverse auctions. However, research has also found that non-contractible elements (including non-contractibility quality, supplier technological investments, information exchange, information diffusion, responsiveness, trust, and flexibility, of inter-organizational relationships) also have great explanatory power for reverse auctions (Ba, Whinston, & Zhang, 2003;Bapna, Jank, & Shmueli, 2008;Ho, Bodoff, & Tam, 2011;Li, Hess, & Valacich, 2006Lim, Sia, Lee, & Benbasat, 2006;Mithas, Jones, & Mitchell, 2008;Webster & Martocchio, 1992). Research has also found implementing information feedback to an auction system to increase the amount of successful trading on the auction websites because it helps build trust, which is critical in electronic auctions (Adomavicius, Curley, Gupta, & Sanyal, 2013;Adomavicius & Gupta, 2005;Ba et al, 2003;Bapna et al, 2003).…”
Section: Electronic Auctions and Bidding Behaviormentioning
confidence: 99%
“…As Tassabehji (2010) recently observed, "the study of e-auctions is still in the early stages and there remains a dearth of substantial empirical research and much more to uncover" [11]. Mithas et al, (2008) There has indeed been a dearth of academic research in the area of reverse auctions [12]. Much of the reason behind the relative paucity of research in the use of reverse auctions in the B2B (business to business) area is due to the limited availability of data, as much of it is proprietary in nature [13].…”
Section: The Growth Of Reverse Auctionsmentioning
confidence: 99%